Microglia/Astrocytes–Glioblastoma Crosstalk: Crucial Molecular Mechanisms and Microenvironmental Factors - Matias, Diana; Balça-Silva, Joana; da Graça, Grazielle C.; Wanjiru, Caroline M.; Macharia, Lucy W.; Nascimento, Carla Pires; Roque, Natalia R.; Coelho-Aguiar, Juliana M.; Pereira, Cláudia M.; Dos Santos, Marcos F.; Pessoa, Luciana S.; Lima, Flavia R. S.; et al. (Frontiers in Cellular Neuroscience, 2018)
In recent years, the functions of glial cells, namely, astrocytes and microglia, have gained prominence in several diseases of the central nervous system, especially in glioblastoma, the most malignant primary brain tumor that leads to poor clinical outcomes. Studies showed that microglial cells or astrocytes play a critical role in promoting glioblastoma growth. Based on the recent findings, the complex network of the interaction between microglial/astrocytes cells and glioblastoma may constitute a potential therapeutic target to overcome tumor malignancy. In the present review, we summarize the most important mechanisms and functions of the molecular factors involved in the microglia or astrocytes – glioblastoma interactions, which is particularly the alterations that occur in the cell’s extracellular matrix and the cytoskeleton. We overview the cytokines, chemokines, neurotrophic, morphogenic, metabolic factors, and non-coding RNAs actions crucial to these interactions. We have also discussed the most recent studies regarding the mechanisms of transportation and communication between microglial/astrocytes – glioblastoma cells, namely through the ABC transporters or by extracellular vesicles. Lastly, we highlight the therapeutic challenges and improvements regarding the crosstalk between these glial cells and glioblastoma.